2005
DOI: 10.1002/andp.200510147
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and the quantum vacuum inertia hypothesis

Abstract: In previous work it has been shown that the electromagnetic quantum vacuum, or electromagnetic zero-point field, makes a contribution to the inertial reaction force on an accelerated object. We show that the result for inertial mass can be extended to passive gravitational mass. As a consequence the weak equivalence principle, which equates inertial to passive gravitational mass, appears to be explainable. This in turn leads to a straightforward derivation of the classical Newtonian gravitational force. We cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 29 publications
2
58
0
1
Order By: Relevance
“…Workers in stochastic electrodynamics (de la Peña & Cetto 1996) have suggested that an electromagnetic pilot wave might arise through the resonant interaction between a microscopic particle's internal vibration and the electromagnetic vacuum field (Boyer 2011). Some have further proposed that the interaction of moving particles with this vacuum field could give rise to a speed-dependent inertial mass, a feature of relativistic mechanics (Haisch & Rueda 2000;Rueda & Haisch 2005). We here explore the relevance of this perspective to the dynamics of walking droplets by inferring their wave-induced added mass.…”
Section: Introductionmentioning
confidence: 99%
“…Workers in stochastic electrodynamics (de la Peña & Cetto 1996) have suggested that an electromagnetic pilot wave might arise through the resonant interaction between a microscopic particle's internal vibration and the electromagnetic vacuum field (Boyer 2011). Some have further proposed that the interaction of moving particles with this vacuum field could give rise to a speed-dependent inertial mass, a feature of relativistic mechanics (Haisch & Rueda 2000;Rueda & Haisch 2005). We here explore the relevance of this perspective to the dynamics of walking droplets by inferring their wave-induced added mass.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical review papers of Margan (nd (a) & nd (b)) are also acknowledge as playing a significant and influential role in the clarification of the thinking on the part of the author. Rueda and Haisch (2005) had considered the idea of quantum vacuum energy continually falling into a massive object (say a planet). They posited that a first intuition might suggest that a continual influx of vacuum energy into a massive body would lead to a steady increase of internal energy with time.…”
Section: Gravity and Quantum Vacuum (Zero Point Energy)mentioning
confidence: 99%
“…A suggestion, put forward by Santos (2012) in which he alluded to the possibility that zero-point energy may be responsible for maintaining the electron stability [Note 2] within atoms via a resonance-type interactions led the author to reexamine the theoretical work of Haisch, Rueda, and Puthoff (1997), Puthoff (2001), Rueda and Haisch (2005). This along with the findings of Rancourt (2011) and Rancourt and Tattersall (2015) led to an interesting conclusion, particularly when entertaining new ideas as to the possible nature of gravity as a pushing force or pressure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations